THE INOVASI PELAYANAN PUBLIK BIDANG PERIZINAN DI KANTOR PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KOTA PALOPO - Ulfa Ulfa (Politeknik STIA LAN Makassar, 2018)
Innovation is the key to success in an organization. Without organizational innovation will not develop, this innovation is intended to improve the performance of public services. Therefore, this study aims to determine the application public service innovation of licencing section in capital investment and integrated one door office of palopo city. The research method used in this study was qualitative research methods, with a descriptive approach. Data obtained from documents, interviews with research informants with a total of 8 people from the Investment Service and One Stop Services in Palopo City and service users representing. The results showed that the innovation of Online Services of Investment Services and One Door Integrated Services of Palopo City was an incremental innovation, but could provide more benefits to the user community. In addition, the implementation had not run optimally, because the people of Palopo were not ready for technology change, and the passive government socialization are the main obstacles in implementing this online system innovation. Therefore, cooperation from all parties is needed. The user community needs to be involved in assessing the government's innovation performance.